Comparative Study Of Graphic Arts In Print For Political Propaganda Between Malaysia And China - Chen, Sin Min (2017)
This research focuses on the use of graphic arts in prints and propaganda between Malaysia and China since the 1950s until 2015. The main objectives are to investigate whether different country of different governing system uses the same visual graphic art for print and propaganda, its future within the context of an increasingly borderless world and the effects of an emergence new technology in digital communication tools. By focusing on the issues of ‘comparable data’ or search for comparable phenomena, 4 major aspects of study have been established for comparative analysis on the roles of graphic arts in prints and propaganda between these two countries.